Bahasa Melayu bahasa dunia : Sejarah singkat / James T. Collins ; alih bahasa, Alma Evita Almanar - COLLINS, James T.; Alma Evita Almanar (Yayasan Obor Indonesia, 2011)
xix, 125 hlm. : ilus. ; 21 cm [3 eks.]